Study on the Structure-Activity Relations of Brominated Hydroxy Diphenyl Ethers Derivatives with Anilines - Luo, Bin; Zhou, Hua-Hong; Yu, Kang-Kang; Wu, Kai-Qun; Chen, Tian; Wang, Yu-Liang (Asian Journal of Chemistry, 2013)
In order to study the influence of anilines on antibacterial activity, eight novel brominated hydroxy diphenyl ethers derivatives were designed and synthesized. The antibacterial activities of the new compounds were tested via agar-well diffusion method in vitro under different concentrations. The results showed the derivatives had antibacterial activities at the concentration 50 μg/mL against Staphylococcus aureus SC and Staphylococcus aureus ATCC26112.